Visual Thinking Ability of Mathematics Education Students on Geometry Transformation Learning Material - Konstansia Hermiati; Siti Suprihatiningsih; Pradipta Annurwanda (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2021)
Solving a problem in geometric transformation that is prioritized is the ability to think visually, this is because visualization is the heart of mathematics to solve a problem, besides that visualization can also make it easier to understand abstract mathematics, and can be used as a strategy for solving mathematical problems to be very simple. This study aims to describe the visual thinking ability of mathematics education students on the material of geometric transformation. The type of research used in this research is descriptive qualitative research. The subjects in this study were 5 students. Written tests related to geometric transformation questions, such as questions, reflections, translations, and dilations were used as data sources in this research. By describing each instrument that has been done by students in accordance with the indicators of visual thinking ability, data analysis techniques are used. The results of this study indicate that students' thinking skills only reach the stage of sorting, searching, and finding. It means only to the acquisition and reasoning. This can be seen from the responses of several students, namely students (1) four stages and three principles of visual thinking ability are achieved. Students can sort out the questions given and look for information to get answers, and can describe and visualize the answers that have been obtained. Student response (2) only did not reach the step of describing and the principle of individuation. This means that students cannot explain and describe answers in the form of pictures or graphs correctly. Student responses (3) only reached the stage of sorting and obtaining or in other words only understanding what was asked. Students in response (4) only did not reach the step of describing and the principle of visualizing/illustrating. So that it can be used as a reference related to visual research, especially on geometry material.